2003
DOI: 10.1111/j.1559-1816.2003.tb01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Partners in Crime: How Liars in Collusion Betray Themselves1

Abstract: The paradigmatic task for participants in studies on deception is to assess veracity on the basis of a single statement. However, in applied contexts, lie catchers are often faced with multiple statements (reported by one or several suspects). To appreciate this mismatch, we conducted a study where each member of 10 truth‐telling pairs and 10 lying pairs (reporting fabricated alibis) was interrogated twice about an alibi. As predicted, lying pair members were more consistent between themselves than were truth‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(134 citation statements)
references
References 31 publications
7
124
3
Order By: Relevance
“…The event was modified from Granhag et al (2003), and reported in detail in Vrij, Leal, Granhag, Mann, Fisher, Hillman, & Sperry (2009). Pairs of participants were recruited under the guise of a study about social interaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The event was modified from Granhag et al (2003), and reported in detail in Vrij, Leal, Granhag, Mann, Fisher, Hillman, & Sperry (2009). Pairs of participants were recruited under the guise of a study about social interaction.…”
Section: Methodsmentioning
confidence: 99%
“…However, when pairs of truth tellers and pairs of liars are given the opportunity to prepare themselves for an interview, they are likely to react differently. Pairs of liars will realise that it is crucial to plan and discuss together the facts of their fabricated story so they "get their stories straight" (Granhag, Strömwall, & Jonsson, 2003). If pairs of liars do not do this they run the risk of each providing statements that are inconsistent with one another, thereby raising doubts about their truthfulness.…”
mentioning
confidence: 99%
“…A process that has been termed 'superficial encoding' (Porter & Yuille, 1996). This theory has had some support, (Granhag & Strömwall, 1999, Granhag, Strömwall, & Jonsson, 2003 and has led to the view that truth tellers create their accounts through reconstruction, whereas liars attempt to accurately repeat a previously rehearsed script. According to these theories, it is these differences in processing and storage that are responsible for systematic and measureable differences in in truthful and fabricated memory accounts (Colwell, HiscockAnisman, Memon, Taylor, & Prewett, 2007).…”
Section: True and Fabricated Memories Pagementioning
confidence: 99%
“…Previous research has shown that varying question format across interviews has helped truth-tellers recall more information in subsequent interviews (Fisher, Brewer, & Mitchell, 2009;Granhag, Strömwall, & Jonsson, 2003), but has hindered liars from repeating information due to the difficult nature of the task (Deeb, Vrij, Hope, Mann, Granhag, & Lancaster, 2017;Leins et al, 2012). Hence, we were interested in exploring whether varying the visuospatial tasks across interviews would have an impact on statements by liars who employ counter-interrogation strategies.…”
Section: The Current Studymentioning
confidence: 99%